Moscow Workers and the 1917 Revolution : Studies of the Russian Institute, Columbia University - Koenker, Diane, 1947- (Book collections on Project MUSE., 1981)
Whereas most Soviet and American scholars of the Russian Revolution have emphasized the great leaders and the great events of 1917, Diane Koenker reverses this trend in a study of the Russian working class.Originally published in 1981.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.